2022
DOI: 10.3390/vaccines10111951
|View full text |Cite
|
Sign up to set email alerts
|

Subnational Gender Inequality and Childhood Immunization: An Ecological Analysis of the Subnational Gender Development Index and DTP Coverage Outcomes across 57 Countries

Abstract: The role of gender inequality in childhood immunization is an emerging area of focus for global efforts to improve immunization coverage and equity. Recent studies have examined the relationship between gender inequality and childhood immunization at national as well as individual levels; we hypothesize that the demonstrated relationship between greater gender equality and higher immunization coverage will also be evident when examining subnational-level data. We thus conducted an ecological analysis examining… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…The Mozambique study identified similar patterns of barriers to vaccination, including the role of gender barriers and power imbalances with health workers. Cross-national quantitative analyses of household survey data show that immunization inequalities are associated with household wealth and maternal education [ 6 ], and that the prevalence of zero-dose children is associated with gender inequality [ 8 ], birth order, birth weight, maternal education, maternal occupation, household wealth, and the number of antenatal care visits [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Mozambique study identified similar patterns of barriers to vaccination, including the role of gender barriers and power imbalances with health workers. Cross-national quantitative analyses of household survey data show that immunization inequalities are associated with household wealth and maternal education [ 6 ], and that the prevalence of zero-dose children is associated with gender inequality [ 8 ], birth order, birth weight, maternal education, maternal occupation, household wealth, and the number of antenatal care visits [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Research exists on the drivers of immunization inequality [ 3 , 4 , 5 , 6 , 7 , 8 , 9 , 10 ], yet most of the existing research focuses either on individual attributes or health system drivers, without analysis of the social and structural processes that produce inequalities [ 11 ]. Recent attention to the role of gender in immunization (in)equity is overdue [ 8 , 12 ] but too often, gender is explored alone, without consideration of how it intersects and interacts with other social, institutional, and structural dimensions of inequality, including social determinants of health. Novel research approaches are needed to reconceptualize immunization inequality—and potential solutions to overcoming it—from caregivers’ lived perspectives.…”
Section: Introductionmentioning
confidence: 99%
“…The Special Issue features research, reviews, and commentaries that span a range of immunization topics and populations. While there is an emphasis on childhood vaccinations [ 15 , 16 , 17 , 18 ]—exploring inequalities in DTP and measles-containing vaccine (MCV) coverage [ 19 , 20 , 21 , 22 , 23 ] and patterns of inequality in unvaccinated or zero-dose children [ 24 , 25 , 26 , 27 , 28 , 29 ]—contributions also cover inequalities in adult immunization [ 30 ], including protection of pregnant women and their newborns against tetanus [ 31 ] and COVID-19 vaccination [ 32 , 33 ].…”
Section: The Special Issue: Monitoring Inequalities and Understanding...mentioning
confidence: 99%
“…An encouraging observation while putting together this Special Issue has been the use of a variety of data sources to assess immunization inequalities. Studies have made use of traditional sources of immunization data like administrative data [ 19 , 23 , 32 ] and population surveys [ 18 , 21 , 22 , 27 , 29 , 30 ] (including Demographic and Health Surveys and/or Multiple Indicator Cluster Surveys [ 15 , 20 , 31 ]), while several other studies explored the potential of novel sources such as geospatial data [ 24 , 25 ], electronic immunization registries [ 34 ], dialogues [ 16 ], country appraisals and reports [ 35 ], and funding proposals [ 26 ]. Three review studies relied on synthesis and structured analyses drawing from a multitude of existing studies [ 17 , 33 , 36 ].…”
Section: The Special Issue: Monitoring Inequalities and Understanding...mentioning
confidence: 99%
See 1 more Smart Citation